2018
DOI: 10.14429/djlit.38.1.11141
|View full text |Cite
|
Sign up to set email alerts
|

Massive Open Online Courses : Hype and Hope

Abstract: The study identifies various issues and challenges faced by massive open online courses (MOOCs) while offering open online courses to vast number of learners. An exhaustive review of literature was taken up to carry out the study. The article reviewed the, issues and challenges faced by MOOCs. MOOC also provides an opportunity to groom the intellectual capacities of people at mass level. The initiative has removed all the barriers of time and space which is much evident in traditional educational system by off… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…It is believed that the government will design and contribute immensely to the growth of knowledge and wisdom from every walks of life wherein three important points to be kept in consideration i.e. equality, accessibility and quality 27 .…”
Section: Reputationmentioning
confidence: 99%
See 1 more Smart Citation
“…It is believed that the government will design and contribute immensely to the growth of knowledge and wisdom from every walks of life wherein three important points to be kept in consideration i.e. equality, accessibility and quality 27 .…”
Section: Reputationmentioning
confidence: 99%
“…The environment of the region also lacks technological backdrops where the full implementation of MOOCs is impossible. Despite the several hindrances in the region, each state has also tried to accept, adopt and implement the latest technology for its development, particularly the educational sector 27 . It is a ray of hope that the region will gradually grow up with the appealing status by moving in with the trending pattern of education where the whole world is adopting and practicing in reality.…”
Section: Reputationmentioning
confidence: 99%
“…Advocates of MOOCs consider them a means of providing quality education through the virtual classroom. Studies have reported that MOOCs expose participants to free higher education course content, empower learners, enable networks among participants, and allow multicultural educational experiences (Clark, Vealé, & Watts, 2017;Nkuyubwatsi, 2013 technological failure, a massive number of students with fewer teachers to handle the courses, pedagogical constraints such as lack of face-to-face interaction, and quality of student assessment, completion rate, language and internet access (Gul, Mahajan, Shafiq, Shafi, & Shah, 2018;Hew & Cheung, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Rees (2013) argues that such online systems can never offer their students the kind of personalised education that dedicated faculty members at universities everywhere can. This could potentially be one of the reasons for dramatic decline in student retention in MOOCs (Gul, 2018), with -only about half of the students who registered ever viewed a lecture and only 4% completed a course‖ (Koller, Ng, Do, & Chen, 2013). This paper will specifically address differentiated learning as an e-learning affordance, in an effort to add value to the entire e-learning experience.…”
Section: Introductionmentioning
confidence: 99%